Mulatto common bean root development for high temperatures - de Lima Silva, Ana Cláudia; Pereira dos Santos, Flávio; de Melo e Silva Neto, Carlos; Ramos Guimarães, Paulo Henrique; Peres Soratto, Rogério [UNESP]; Pereira Torga, Paula (Springer Nature, 2024)
Temperature is a determining factor for common bean production in several regions of Brazil. This study formed a thematic collection for high temperatures of mulatto common bean from the Active Germplasm Bank of Embrapa Rice and Beans. The experiments were conducted under field conditions in suitable temperature environment (STE), and in a high temperature environment (HTE) where 94 accessions were evaluated. Joint analysis of the agronomic data obtained in these experiments, together with the database of ecogeographical and morphological characterization of mulatto common bean accessions constituted the study to elaborate the thematic collection for high temperature conditions, totaling 30 accessions, of which 28 had their root growth characterized in a rhizotron system in a greenhouse. Data analysis identified superior genotypes in relation to the studied characteristics, but there were no significant correlations. It was observed that the grain yield averages per accession in the field experiments in STE and in HTE of the 96 accessions were 2068.9 and 1227.2 kg ha−1, respectively, altered to the value of 2400.8 and 1271.5 kg ha−1 when selecting the 30 accessions which compose the thematic collection. The root architecture varied for the different evaluated accessions. The resulting thematic core collection potentially reflects the maximum diversity of mulatto common beans in a smaller sample size for high temperatures.
Keywords: Adaptation; Climate change; Diversity; Genetic resources; Phaseolus vulgaris; Thematic collection